Initial conditions in chaotic inflation with modified gravity - Gorbunov Dmitry (EPJ Web of Conferences, 2017)
Evolution in chaotic inflationary models begins at a high energy density with semi-classical initial conditions presumably consistent with a universal quantum nature of all the fundamental interactions: each quantum contributes the same amount to the energy density. There is an upper limit on this amount inherent in the approach, ensuring that all the quanta are inside the weak-coupling domain. This issue is investigated in realistic models of modified gravity, R2- and Higgs-inflations, with emphasize on the specific change of the initial conditions with metric frame, while all the quanta still contribute equal parts. This illustrates that inflationary models with flat potential may be natural.